Fatty acid composition of adipose tissue and blood in humans and its use as a biomarker of dietary intake. - Hodson, L; Skeaff, C; Fielding, B (2008)
Accurate assessment of fat intake is essential to examine the relationships between diet and disease risk but the process of estimating individual intakes of fat quality by dietary assessment is difficult. Tissue and blood fatty acids, because they are mainly derived from the diet, have been used as biomarkers of dietary intake for a number of years. We review evidence from a wide variety of cross-sectional and intervention studies and summarise typical values for fatty acid composition in adipose tissue and blood lipids and changes that can be expected in response to varying dietary intake. Studies in which dietary intake was strictly controlled confirm that fatty acid biomarkers can complement dietary assessment methodologies and have the potential to be used more quantitatively. Factors affecting adipose tissue and blood lipid composition are discussed, such as the physical properties of triacylglycerol, total dietary fat intake and endogenous fatty acid synthesis. The relationship between plasma lipoprotein concentrations and total plasma fatty acid composition, and the use of fatty acid ratios as indices of enzyme activity are also addressed.